The Obesity-Fertility Protocol: a randomized controlled trial assessing clinical outcomes and costs of a transferable interdisciplinary lifestyle intervention, before and during pregnancy, in obese infertile women. Issue 1 (December 2015) - Duval, Karine; Langlois, Marie-France; Carranza-Mamane, Belina; Pesant, Marie-Hélène; Hivert, Marie-France; Poder, Thomas; Lavoie, Hélène; Ainmelk, Youssef; St-Cyr Tribble, Denise; Laredo, Sheila; Greenblatt, Ellen; Sagle, Margaret; et al.
Abstract Background Obesity in infertile women increases the costs of fertility treatments, reduces their effectiveness and increases significantly the risks of many complications of pregnancy and for the newborn. Studies suggest that even a modest loss of 5–10 % of body weight can restore ovulation. However, there are gaps in knowledge regarding the benefits and cost-effectiveness of a lifestyle modification program targeting obese infertile women and integrated into the fertility clinics. This study will evaluate clinical outcomes and costs of a transferable interdisciplinary lifestyle intervention, before and during pregnancy, in obese infertile women. We hypothesize that the intervention will: 1) improve fertility, efficacy of fertility treatments, and health of mothers and their children; and 2) reduce the cost per live birth, including costs of fertility treatments and pregnancy outcomes. Methods/Design Obese infertile women (age: 18–40 years; BMI ≥30 kg/m2 or ≥27 kg/m2 with polycystic ovary syndrome) will be randomised to either a lifestyle intervention followed by standard fertility treatments after 6 months if no conception has been achieved (intervention group) or standard fertility treatments only (control group). The intervention and/or follow-up will last for a maximum of 18 months or up to the end of pregnancy. Evaluation visits will be planned every 6 months where different outcome measures will be assessed. The primary outcome will be live-birth rates at 18 months. The secondary outcomes will be sub-divided into four categories: lifestyle and anthropometric, fertility, pregnancy complications, and neonatal outcomes. Outcomes and costs will be also compared to similar women seen in three fertility clinics across Canada. Qualitative data will also be collected from both professionals and obese infertile women. Discussion This study will generate new knowledge about the implementation, impacts and costs of a lifestyle management program in obese infertile women. This information will be relevant for decision-makers and health care professionals, and should be generalizable to North American fertility clinics. Trial registration ClinicalTrials.govNCT01483612 . Registered 25 November 2011.